Varieties of anomalous experience : examining the scientific evidence - Cardeña, Etzel; Lynn, Steven J.; Krippner, Stanley, 1932- (Dissociation, trauma, memory, and hypnosis book series., 2014)
"Mainstream psychology has mostly ignored or even derided anomalous experiences after an initial interest at the end of the 19th century and beginning of the 20th. They have been examples of what postmodernists refer to as "the other," phenomena that fall between the cracks of the house built by contemporary mainstream psychology. However, psychology now has the maturity and breadth required to take a serious look at unusual but important experiences. We define an anomalous experience (AE) as an uncommon experience (e.g., synesthesia), or one that, although it may be experienced by a significant number of persons (e.g., psi experiences), is believed to deviate from ordinary experience or from the usually accepted explanations of reality according to Western mainstream science. The focus of this book is on experiences, not on testing the ontological nature of such experiences. Thus, for instance, the possibility of veridical psi occurrences is mentioned in the section of explanatory theories in the psi-related experiences chapter, but its focus is on the experiences people have"--Chapter. (PsycINFO Database Record (c) 2013 APA, all rights reserved).